SWARNA PRASHAN HAS A PRESSING NEED FOR TIME AMONG YOUNG ONES - CHATURVEDI, CHAKRAPANI; VYAS, PREM PRAKASH; CHATURVEDI, SAKSHI (International Journal of Current Pharmaceutical Research, 2022)
Covid-19 calls for immunity boosters especially among children and the young generation. Ayurvedic preparations are another safer choice to build immunity naturally. Swarna Prashan is a safe ayurvedic combination that is beneficial for the normal growth and development of a child. Swarna Prashan is introducing Swarna (GOLD METAL) alone or along with herbs in the liquid form as an oral vaccine by children. Swarna Prashan is one of the samskaras in Ayurveda. Swarna Prashan is initiated from infancy till Adolescence. To review the components of swarnaprashna, clinical trials, and evidence of benefits for children. Ayurveda has deep roots for the Current and old method of introduction of Swarnaprashna among children below 16 y of age group in India. Overall results of all studies showed improved growth and development after the introduction of Swarna Prashan within a year without any side effects and a happy childhood which shows not only health but also wellbeing.